Early Mesolithic activities at ancient Lake Duvensee, northern Germany. (February 2019) - Groß, Daniel; Lübke, Harald; Schmölcke, Ulrich; Zanon, Marco
The ancient lake Duvensee in Schleswig-Holstein, Germany, is one of the prime locations in northern Europe for early Holocene research. Archaeological sites on the former lakeshore provide vivid illustrations of early Mesolithic life, with bark mats and other organic finds preserved, including evidence for the extensive use of hazelnuts. Although the area has been the subject of research for almost 100 years, a coherent summary of these discoveries has not yet been written. Here we review past research at Duvensee, and give some prospects for further research. We show that the Duvensee sites varied in their structure and chronology. While only a limited number of sites can be connected to hazelnut exploitation, some of them show signs of hafting and retooling and other domestic activities. At a few sites, specific hearths were excavated which can be connected with hazelnut roasting and other subsistence activities. Finally, we show that while most earlier studies focused almost exclusively on archaeological research questions, Duvensee has the potential to reveal not only transformations in human behaviour, but also environmental changes at a detailed scale; we therefore argue for a more holistic perspective and multidisciplinary approach to reconstructing prehistoric landscapes and cultural transformations.